Foam stabilizer raw material system, method for preparing nano foam stabilizer, nano foam stabilizer and application
By using inorganic nanoparticles and organic monomers in natural gas oil flooding technology to prepare nanofoam stabilizers, the problem of insufficient temperature and salt resistance of foam stabilizers is solved, and the stability of foam under high temperature and high mineralization conditions is improved. and sealing ability, effectively prevent and control air traversal.
Patent Information
- Application Number
- CN202310792735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-29
AI Technical Summary
In the existing natural gas oil flooding technology, the foam stabilizer has insufficient temperature and salt resistance, resulting in poor stability in high-temperature and high-mineralization formations, and it is impossible to effectively prevent and control gas traversal.
Using a combined raw material system of inorganic nanoparticles, organic monomers, initiators, catalysts and hydrophobic modifiers, nanofoam stabilizers are prepared through grafting and polymerization reactions. The nanoparticles have hydrophobic groups and electroneutral hydrophilic polymerization. substance groups enhance the stability of the foam.
It improves the stability of the foam under high temperature and high mineralization conditions, extends the half-life and volume of the foam, enhances the sealing ability in deep strata, and effectively prevents and controls air trajectory.
Smart Images

Figure CN119219865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of natural gas oil recovery, and in particular to a foam stabilizer raw material system, a method for preparing a nano foam stabilizer, a nano foam stabilizer and an application thereof. Background Art
[0002] As one of the tertiary oil recovery technologies, natural gas flooding has unique advantages in terms of oil recovery efficiency and sweep efficiency, and has been highly concerned at home and abroad in recent years. In addition, many oilfield units also have the ability to exploit natural gas, which guarantees a rich gas source for this technology. However, due to the low mobility of natural gas, when it is used in heterogeneous formations with developed fractures or large permeability differences, there is a risk of early gas breakthrough or gas channeling that is more significant than water injection, which not only greatly reduces the oil recovery rate, but also poses a serious risk. Therefore, the prevention and control of gas channeling plays a vital role in the development of natural gas flooding in the above-mentioned oil reservoirs.
[0003] Foam flooding is an effective method to prevent and delay gas channeling. When foam passes through heterogeneous formations, it will preferentially enter the high permeability layer, and achieve the purpose of plugging through the superimposed Jamin effect, which can effectively improve the formation heterogeneity and improve the subsequent gas drive sweep efficiency. Since foam is a thermodynamically unstable system, it will break in the formation, affecting the effect and validity period of gas channeling control. Therefore, the foam stabilization system is usually a necessary component in the composition of the foam liquid. In recent years, nanoparticles have gradually been used as a foam stabilization system.
[0004] There have been anionic surfactants (SDS) and hydrophobic nanosilica (SiO 2 The experimental study on the co-stabilization of foam by hydrophobic nano-SiO2 particles showed that the hydrophobic nano-SiO2 particles can enhance the stability of foam. 2 There is a hydrophobic interaction between the hydrophobic groups of nano-SiO 2 They are attracted to the gas-liquid interface to form a skeleton structure, increase the mechanical strength of the foam, and stabilize the foam. However, as the temperature and mineralization increase, the stability of the nanoparticles will be greatly reduced, and even precipitation will occur, which will not be able to play the role of stabilizing the foam. 2 Both the SDS head group and the SiO2 head group have negative charges, and there is also an electrostatic repulsion between the two, which will offset part of the attraction between the two and weaken the nano-SiO2 2 Adsorption at the gas-liquid interface is also detrimental to the stability of the foam. 2The mixed system of nanoparticles and anionic-nonionic surfactant fatty alcohol polyoxyethylene ether sodium sulfate plays a role in stabilizing natural gas foam. However, during the deep migration process in the formation, the nanoparticles are easily separated from the surfactant and cannot play a role in stabilizing the foam in the deep formation. Summary of the invention
[0005] The main purpose of the present invention is to provide a foam stabilizer raw material system, a method for preparing a nano foam stabilizer, a nano foam stabilizer and an application thereof, so as to solve the problem of insufficient temperature and salt resistance of the foam stabilizer in the prior art.
[0006] To achieve the above object, according to one aspect of the present invention, a foam stabilizer raw material system is provided, which comprises: inorganic nanoparticles, organic monomers, initiators, catalysts and hydrophobic modifiers; wherein the organic monomers have electrically neutral hydrophilic groups.
[0007] Furthermore, the inorganic nanoparticles are nano-SiO 2 、Nano-TiO 2 , nano ZnO and nano Al 2 O 3 Any one or more of the above, preferably, the particle size of the inorganic nanoparticles is 20 to 100 nm;
[0008] Preferably, the initiator is 2,3-dihydroxypropyl propyl ether triethoxysilane;
[0009] Preferably, the hydrophobic modifier includes any one or more of trimethylmonoethoxysilane, dimethyldiethoxysilane, isopropyltriethoxysilane, isobutyltrimethoxysilane and n-octyltriethoxysilane;
[0010] Preferably, the catalyst comprises any one or more selected from potassium diperiodate copper and potassium diperiodate nickel;
[0011] Preferably, the raw material system includes 5 to 15 parts by weight of inorganic nanoparticles, 1.0 to 2.0 parts by weight of an initiator, 3.0 to 10.0 parts by weight of an organic monomer, 0.3 to 0.6 parts by weight of a catalyst, and 0.8 to 2.0 parts by weight of a hydrophobic modifier;
[0012] Preferably, the raw material system also includes a reaction medium, and the reaction medium is water.
[0013] According to another aspect of the present invention, a method for preparing a nano foam stabilizer using the above raw material system is provided, the method comprising: step S1, dispersing inorganic nanoparticles in water, adjusting the pH value to alkaline, adding an initiator to the system to form a first mixed solution for reaction, and after the reaction is completed, separating the solid to obtain a first intermediate; step S2, dispersing the first intermediate and an organic monomer in water, introducing an inert gas to deoxygenate, adding a catalyst to form a second mixed solution for polymerization reaction, and after the polymerization reaction is completed, separating the solid to obtain a second intermediate; step S3, dispersing the second intermediate in water, adding a hydrophobic modifier to form a third mixed solution for modification reaction, and after the modification reaction is completed, obtaining a nano foam stabilizer.
[0014] Furthermore, in step S1, the mass percentage of the inorganic nanoparticles in the mixed solution is 5-15%, and the mass percentage of the initiator is 1.0-2.0%;
[0015] Preferably, the pH value is 8.0 to 9.0;
[0016] Preferably, the initiator is added in the form of an initiator aqueous solution, preferably the initiator aqueous solution is added in the form of dropwise addition, preferably an alkaline solution is added during the dropwise addition to adjust the pH value to alkaline, and more preferably, the pH value is adjusted to 8.0 to 9.0 during the dropwise addition;
[0017] Preferably, the alkaline solution is any one or more of a sodium hydroxide aqueous solution or a sodium carbonate aqueous solution.
[0018] Furthermore, the reaction temperature in step S1 is 70-80° C., and preferably, after the initiator aqueous solution is added dropwise, the temperature is raised to the reaction temperature;
[0019] Preferably, the reaction time is 15 to 20 hours.
[0020] Furthermore, in the second mixed solution, the mass fraction of the first intermediate is 5-15%, the mass fraction of the organic monomer is 3.0-10.0%, and the mass fraction of the catalyst is 0.3-0.6%;
[0021] Preferably, the polymerization reaction temperature is 50-60° C., and preferably the polymerization reaction time is 5-8 h.
[0022] Furthermore, the mass fraction of the second intermediate in the third mixed solution is 8 to 15%, and the mass fraction of the hydrophobic modifier is 0.5 to 2.0%;
[0023] Preferably, the temperature of the modification reaction is 60-70° C., and the time of the modification reaction is preferably 20-25 h.
[0024] According to another aspect of the present application, a nano foam stabilizer is provided, and the nano foam stabilizer is prepared by any of the above methods.
[0025] According to another aspect of the present application, a foam flooding system is provided, wherein the foam flooding system comprises the above-mentioned nano foam stabilizer.
[0026] According to another aspect of the present application, there is provided an application of the above-mentioned foam flooding system in gas flooding, wherein the gas is preferably natural gas.
[0027] By applying the technical solution of the present invention, the foam stabilizer prepared by the system is composed of nanoparticles, which not only have hydrophobic groups on them, which can produce hydrophobic interactions with the tail of the foaming agent, but also have electrically neutral hydrophilic polymer groups on the particles, which can play a role in temperature and salt resistance on the one hand; on the other hand, compared with some anionic polymers, such as 2-acrylamide-2-methylpropanesulfonic acid sodium polymer, it is beneficial to reduce or avoid charge repulsion with the surfactant head group, promote the adsorption of nanoparticles at the gas-liquid interface, and then help improve the stability of the foam. In this way, when it is carried by injected water, it is beneficial to its smooth migration in high-temperature and high-mineralization reservoirs, and foam is generated in the deep part of the formation during the gas injection process. When it is used in combination with a foaming agent, it can have a higher resistance factor than using a foaming agent alone, and achieve the function of deep plugging and delaying gas channeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0029] Figure 1 The dynamic light scattering (DLS) particle size distribution diagram of the nano foam stabilizer of Example 1 of the present invention in simulated salt water (mineralization degree is 100000 mg / L) is shown;
[0030] Figure 2 The X-ray photoelectron spectrum of the nano foam stabilizer of Example 1 of the present invention is shown;
[0031] Figure 3 The thermogravimetric analysis curve of the nano foam stabilizer of Example 1 of the present invention is shown;
[0032] Figure 4 The natural gas injection resistance factor diagram of the oil displacement system in Application Example 1 of the present invention and the control group is shown. DETAILED DESCRIPTION
[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0034] As analyzed in the background technology of this application, there is a problem in the prior art that the foam stabilizer has insufficient heat and salt resistance, and the foam stabilization effect in deep formations cannot meet the demand. In order to solve this problem, this application provides a foam stabilizer raw material system, a method for preparing a nano foam stabilizer, a nano foam stabilizer and its application.
[0035] According to one embodiment of the present application, a foam stabilizer raw material system is provided, which includes: inorganic nanoparticles, an organic monomer initiator, a catalyst and a hydrophobic modifier; wherein the organic monomer has an electrically neutral hydrophilic group.
[0036] The foam stabilizer prepared by this system is composed of nanoparticles, which not only have hydrophobic groups on them, which can produce hydrophobic interactions with the tail of the foaming agent, but also have electrically neutral hydrophilic polymer groups on the particles, which can play a role in temperature and salt resistance on the one hand; on the other hand, compared with some anionic polymers, such as 2-acrylamide-2-methylpropanesulfonic acid sodium polymer, it is conducive to reducing or avoiding charge repulsion with the surfactant head group, promoting the adsorption of nanoparticles at the gas-liquid interface, and thus helping to improve the stability of the foam. In this way, when it is carried by injected water, it is conducive to its smooth migration in high-temperature and high-mineralization reservoirs, and generates foam in the deep formation during the gas injection process. When it is used in combination with a foaming agent, it can have a higher resistance factor than using a foaming agent alone, achieving the function of deep plugging and delaying gas channeling.
[0037] The inorganic nanoparticles can be selected from the prior art. In some embodiments of the present application, the inorganic nanoparticles are nano-SiO 2 、Nano-TiO 2 , nano ZnO and nano Al 2 O 3 Preferably, the particle size of the inorganic nanoparticles is 20 to 100 nm, which can further enhance the foam stabilizing performance of the foam stabilizer.
[0038] The above-mentioned organic monomer with an electrically neutral hydrophilic group can be selected from the prior art. In some preferred embodiments of the present application, in order to further improve the foam stabilizing performance of the foam stabilizer under high temperature and high salt conditions, the above-mentioned organic monomer includes any one or more of 2,3-dihydroxypropyl methacrylate, N-(2,3-dihydroxypropyl) methacrylamide, 3-methacryloylpropyl-dimethyl-3-sulfonic acid propyl ammonium salt and 3-methacrylate propyl-dimethyl-3-sulfonic acid propyl ammonium salt.
[0039] In some typical embodiments of the present application, the initiator is 2,3-dihydroxypropyl propyl ether triethoxysilane, which can promote the polymerization of the organic monomers to form a foam stabilizer with better foam stabilization function, especially with a significant impact on the temperature and salt resistance.
[0040] The above-mentioned hydrophobic modifier can be selected from the prior art without special requirements. For example, the hydrophobic modifier includes but is not limited to any one or more of trimethylmonoethoxysilane, dimethyldiethoxysilane, isopropyltriethoxysilane, isobutyltrimethoxysilane and n-octyltriethoxysilane.
[0041] In some preferred embodiments of the present application, the above-mentioned catalyst includes any one or more selected from potassium diperiodate copper (III) and potassium diperiodate nickel (IV), which can better work together with the initiator to promote the polymerization of organic monomers and significantly improve the foam stabilizing performance of the foam stabilizer.
[0042] In some embodiments of the present application, in order to better exert the synergistic effect between the components, the raw material system includes 5 to 15 parts by weight of inorganic nanoparticles, 1.0 to 2.0 parts by weight of initiator, 3.0 to 10.0 parts by weight of organic monomer, 0.3 to 0.6 parts by weight of catalyst and 0.8 to 2.0 parts by weight of hydrophobic modifier.
[0043] Preferably, the raw material system also includes a reaction medium, and the reaction medium is water.
[0044] According to another embodiment of the present application, a method for preparing a nano foam stabilizer using the above-mentioned raw material system is provided, and the method comprises: step S1, dispersing inorganic nanoparticles in water, adjusting the pH value to alkaline, adding an initiator to the system to form a first mixed solution for reaction, and after the reaction is completed, separating the solid to obtain a first intermediate; step S2, dispersing the first intermediate and an organic monomer in water, introducing an inert gas for deoxygenation, adding a catalyst to form a second mixed solution for polymerization reaction, and after the polymerization reaction is completed, separating the solid to obtain a second intermediate; step S3, dispersing the second intermediate in water, adding a hydrophobic modifier to form a third mixed solution for modification reaction, and after the modification reaction is completed, obtaining a nano foam stabilizer.
[0045] The above preparation method is prepared by first grafting a silane coupling agent initiator on an inorganic nanoparticle, then under the action of a catalyst, a hydrophilic monomer undergoes a polymerization reaction on the particle surface, and finally the particle is grafted with a hydrophobic silane coupling agent. The nano foam stabilizer prepared by the above preparation method not only has a hydrophobic group that can produce a hydrophobic interaction with the tail of the foaming agent, but also has an electrically neutral hydrophilic polymer group on the particle, which can play a role in temperature and salt resistance on the one hand; on the other hand, compared with some anionic polymers, such as 2-acrylamide-2-methylpropane sulfonate sodium polymer, it is beneficial to reduce or avoid charge repulsion with the surfactant head group, promote the adsorption of nanoparticles at the gas-liquid interface, and thus help improve the stability of the foam. When it is used in combination with a foaming agent, it can have a higher resistance factor than the foaming agent alone, which is beneficial to its smooth migration in high-temperature and high-mineralization reservoirs, and generates foam in the deep part of the formation during the gas injection process, realizing the function of deep plugging and delaying gas channeling. Moreover, the reactions in the preparation method are all water-phase reactions, no organic solvents are used, and the environmental pollution is small.
[0046] In some embodiments of the present application, in step S1, the mass percentage of inorganic nanoparticles in the mixed solution is 5-15%, and the mass percentage of the initiator is 1.0-2.0%. This concentration and ratio are conducive to the grafting reaction of the initiator and the inorganic nanoparticles. In some preferred embodiments of the present application, in step S1, the pH value is adjusted to 8.0-9.0, which has a more obvious promoting effect on the grafting reaction of the initiator and the inorganic nanoparticles, and can significantly improve the performance of the prepared foam stabilizer.
[0047] In some typical embodiments of the present application, in order to further improve the efficiency of the grafting reaction in the above step S1, the initiator is added in the form of an initiator aqueous solution; preferably, the initiator aqueous solution is added in the form of drops, so that the initiator can be dispersed more evenly on the surface or around the inorganic nanoparticles to form a more uniform graft, and further enable the subsequent organic monomer to form a uniform polymer on the surface of the inorganic nanoparticles, which can play a better foam stabilizing effect. In some embodiments of the present application, in order to further improve the above effect, the above initiator aqueous solution is slowly added dropwise under stirring and gas protection to make the initiator more evenly dispersed in the system. Exemplarily, in the laboratory preparation process, the dripping speed of the initiator aqueous solution is 1.0 to 1.5 mL / min.
[0048] In some preferred embodiments of the present application, an alkaline solution is added during the dropwise addition process to adjust the pH value to alkaline, and more preferably the pH value is adjusted to 8.0-9.0 during the dropwise addition process, which is beneficial to further improve the effect of the grafted product; the alkaline solution can be selected from the prior art, including but not limited to any one or more of sodium hydroxide aqueous solution or sodium carbonate aqueous solution.
[0049] In some embodiments of the present application, the reaction temperature in step S1 is 70-80°C, and the grafting effect is better. Preferably, after the initiator aqueous solution is added dropwise, it is heated to the reaction temperature, which is conducive to forming a more uniform initiator graft on the surface of the inorganic nanoparticles. Preferably, the reaction time after the initiator is added dropwise is 15-20 hours, so that the initiator and the inorganic nanoparticles are fully combined.
[0050] In some embodiments of the present application, step S1 further includes washing the separated solid with water and then drying to obtain the above-mentioned first intermediate, which can remove the alkali adhering to the surface of the inorganic particles or the ungrafted initiator to avoid interference with subsequent reactions.
[0051] In some embodiments of the present application, the mass fraction of the first intermediate in the above-mentioned second mixed solution is 5-15%, the mass fraction of the organic monomer is 3.0-10.0%, and the mass fraction of the catalyst is 0.3-0.6%, which is beneficial to improve the performance of the foam stabilizer. Preferably, the temperature of the polymerization reaction is 50-60°C, and the time of the polymerization reaction is 5-8h. The second intermediate formed can further improve the foam stabilizing performance of the foam stabilizer while taking into account the efficiency of the polymerization reaction. In some embodiments of the present application, after the catalyst is added, the formed second mixed solution is raised to the reaction temperature for polymerization. In some embodiments of the present application, after the polymerization reaction is completed, the separated solid is washed with water and dried to obtain a second intermediate, and impurities attached to the second intermediate are removed.
[0052] In step S3, a hydrophobic group is grafted onto the second intermediate to perform hydrophobic modification. In some embodiments of the present application, the mass fraction of the second intermediate in the third mixed solution is 8-15%, and the mass fraction of the hydrophobic modifier is 0.5-2.0%, which is beneficial to improving the foam stabilization performance of the product. Preferably, the temperature of the modification reaction is 60-70°C, and the time of the modification reaction is 20-25h, which can form a foam stabilizer with good hydrophobic modification effect.
[0053] According to another embodiment of the present application, a nano foam stabilizer is provided, which is prepared by any of the above methods. The nano foam stabilizer is prepared by first grafting a silane coupling agent-type initiator on an inorganic nanoparticle, then polymerizing a hydrophilic monomer on the particle surface under the action of a catalyst, and finally grafting a hydrophobic silane coupling agent on the particle. The nano foam stabilizer prepared by the above preparation method not only has a hydrophobic group that can produce a hydrophobic interaction with the tail of the foaming agent, but also has an electrically neutral hydrophilic polymer group on the particle, which can play a role in temperature and salt resistance on the one hand; on the other hand, compared with some anionic polymers, such as 2-acrylamide-2-methylpropanesulfonic acid sodium polymer, it is beneficial to reduce or avoid charge repulsion with the surfactant head group, promote the adsorption of nanoparticles at the gas-liquid interface, and thus help improve the stability of the foam. In this way, when it is carried by injected water, it is conducive to its smooth migration in high-temperature and high-mineralization reservoirs, and foam is generated deep in the formation during the gas injection process. When it is used in combination with a foaming agent, it can have a higher resistance factor than using a foaming agent alone, thereby achieving the function of deep plugging and delaying gas channeling.
[0054] According to another embodiment of the present application, a foam flooding system is provided, which includes the above-mentioned nano foam stabilizer. Since the foam flooding system contains the above-mentioned nano foam stabilizer, it has a higher resistance factor when used in combination with a foaming agent, which is conducive to its smooth migration in high-temperature and high-mineralization reservoirs, and generates foam in the deep part of the formation during the gas injection process, thereby achieving the functions of deep plugging and delaying gas channeling.
[0055] According to another embodiment of the present application, an application of the above foam flooding system in gas flooding is provided. The above nano foam stabilizer is not only temperature-resistant and salt-resistant, but also has a hydrophobic effect with the foaming agent and avoids or weakens the charge repulsion effect, thereby having a good foam stabilization function and is suitable for blocking gas channeling in deep formations.
[0056] The foam flooding system can be applied to various gas floodings, including but not limited to air flooding, natural gas flooding and carbon dioxide flooding. In particular, when natural gas is used as the flooding gas, the foam stabilizing effect of the nano foam stabilizer is particularly improved.
[0057] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0058] The 2,3-dihydroxypropyl propyl ether triethoxysilane used in the examples of the present application was prepared by the following method: first, 100 mL of a dilute hydrochloric acid aqueous solution with a pH of 2.0 to 3.0 was prepared, and then 1.5 g of γ-glycidyloxypropyl triethoxysilane was added thereto, and stirred for 20 to 30 minutes to obtain an aqueous solution of 2,3-dihydroxypropyl propyl ether triethoxysilane. Example 1
[0059] (1) SiO 2 Nanoparticles (15 g, D = 30 nm) were added to 50 mL of NaOH aqueous solution (pH = 9.0), and after being evenly dispersed, 1.6 g of 2,3-dihydroxypropyl propyl ether triethoxysilane aqueous solution (100 mL) was added dropwise under the protection of inert gas. During the addition, 2 M NaOH aqueous solution was added to the system to maintain the pH value of the system at 9.0. After the addition was completed, the system was heated to 80 ° C, and then the reaction was carried out at a constant temperature for 20 hours. After the reaction was completed, the system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 1;
[0060] (2) Add H 2 O (100 mL), intermediate 1 (10.0 g) and 3-methacryloylpropyl-dimethyl-3-sulfonic acid propyl ammonium salt (8.8 g), after stirring evenly, nitrogen was introduced to deoxygenate for 30 min, and then 0.87 g of potassium dipyrodecanoate (III) was added, and the temperature was raised to 50 ° C. After reacting for 6 h under continuous nitrogen introduction, the nitrogen introduction was stopped and the polymerization reaction was terminated. The system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 2;
[0061] (3) Add intermediate 2 (5.0 g) and water (40 mL) to a flask in sequence, adjust the pH value of the system to 9.0 with an aqueous NaOH solution, and add 10 mL of a hydrochloric acid solution (pH = 2.0) of isobutyltrimethoxysilane (0.5 g) dropwise under nitrogen protection. After the addition is completed, the system is heated to 70°C and reacted at this temperature for 20 hours. After separation, the solid is obtained, which is washed with water and dried to obtain a nano foam stabilizer.
[0062] The dynamic light scattering (DLS) particle size distribution of the nano foam stabilizer prepared in this example in simulated saline (mineralization degree is 100000 mg / L) is as follows: Figure 1 Its X-ray photoelectron spectroscopy and thermogravimetric analysis are shown in Figure 2 and Figure 3 shown.
[0063] Example 2
[0064] (1) Al 2 O 3Nanoparticles (12 g, D = 25-30 nm) were added to 50 mL of NaOH aqueous solution (pH = 9.0), and after being evenly dispersed, 2.0 g of 2,3-dihydroxypropyl propyl ether triethoxysilane aqueous solution (100 mL) was added dropwise under the protection of inert gas. During the addition, 2M NaOH aqueous solution was added to the system to maintain the pH value of the system at 9.0. After the addition was completed, the system was heated to 80°C, and then the reaction was carried out at a constant temperature for 15 hours. After the reaction was completed, the system was separated to obtain a solid, which was washed with water and dried to obtain the intermediate 1′;
[0065] (2) Add H 2 O (100 mL), intermediate 1′ (10.0 g) and N-(2,3-dihydroxypropyl)methacrylamide (7.0 g), stirred evenly, introduced nitrogen to deoxygenate for 30 min, then added 0.80 g of potassium dipyrodecanoate (III), and heated to 50°C. After reacting for 6 h under continuous nitrogen introduction, nitrogen introduction was stopped and the polymerization reaction was terminated. The system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 2′;
[0066] (3) The intermediate 2′ (5.0 g) and water (40 mL) were added to the flask in sequence, and the pH value of the system was adjusted to 9.0 by using an aqueous NaOH solution. Under nitrogen protection, 10 mL of a hydrochloric acid solution (pH = 2.0) of n-octyltriethoxysilane (0.75 g) was added dropwise. After the addition was completed, the system was heated to 60° C. and reacted at this temperature for 25 h. After that, a solid was separated and washed with water and dried to obtain a nano foam stabilizer.
[0067] Example 3
[0068] The difference from Example 1 is that in step (1), SiO 2 Nanoparticles (15 g, D=30 nm) were added to 50 mL of NaOH aqueous solution (pH=8.0), and during the dropwise addition, 2 M NaOH aqueous solution was added to maintain the pH value of the system at 8.0.
[0069] Example 4
[0070] The difference from Example 1 is that in step (1), the pH value of the system is no longer adjusted during the dropwise addition process, and the pH value of the system is 3.0-4.0 after the dropwise addition is completed.
[0071] Example 5
[0072] The difference from Example 1 is that in step (1), SiO 2Nanoparticles (15 g, D=30 nm) were added to 50 mL of NaOH aqueous solution (pH=10.0), and during the dropwise addition, the pH value of the system was maintained at 10.0 by adding 2 M NaOH aqueous solution to the system.
[0073] Example 6
[0074] The difference from Example 1 is that in step (1), SiO 2 Nanoparticles (15 g, D=30 nm) were added into 50 mL of water, and the pH value of the system was not adjusted during the addition.
[0075] Example 7
[0076] The difference from Example 1 is that in step (1), SiO 2 Nanoparticles (15 g, D = 30 nm) were added to 20 mL of NaOH aqueous solution (pH = 8.0). After being evenly dispersed, 2.0 g of 2,3-dihydroxypropyl propyl ether triethoxysilane aqueous solution (40 mL) was added dropwise under the protection of inert gas. During the addition, the pH value of the system was maintained at 9.0 by adding 2 M NaOH aqueous solution to the system, and a total of 0.1 to 0.2 mL was added dropwise; the subsequent treatment steps were the same as those in Example 1.
[0077] Example 8
[0078] The difference from Example 1 is that in step (1), the isothermal reaction time is 10 h.
[0079] Example 9
[0080] The difference from Example 1 is that in step (1), the temperature is raised to 60°C, that is, the reaction temperature is 60°C.
[0081] Example 10
[0082] The difference from Example 1 is that in step (2), the amount of water added to the flask is 50 mL.
[0083] Comparative Example 1
[0084] (1) SiO2 nanoparticles (15 g, D = 30 nm) and 3-methacryloylpropyl-dimethyl-3-sulfonic acid propyl ammonium salt (8.8 g) were added to H under stirring. 2O (100 mL), after being evenly dispersed, 1.6 g of an aqueous solution of 2,3-dihydroxypropyl propyl ether triethoxysilane (100 mL) was added dropwise thereto under the protection of an inert gas, and after being evenly stirred, nitrogen was bubbled for 30 min, and then 0.87 g of potassium dipyrocopper (III) was added, and the temperature was raised to 50°C. After reacting for 6 h under continuous nitrogen flow, the nitrogen flow was stopped and the polymerization reaction was terminated. The system was separated to obtain a solid, which was washed with water and dried to obtain an intermediate 2;
[0085] (2) Add intermediate 2 (5.0 g) and water (40 mL) to a flask in sequence, adjust the pH value of the system to 9.0 with an aqueous NaOH solution, and add 10 mL of a hydrochloric acid solution (pH = 2.0) of isobutyltrimethoxysilane (0.5 g) dropwise under nitrogen protection. After the addition is completed, the system is heated to 70°C and reacted at this temperature for 20 hours. After separation, a solid is obtained, which is washed with water and dried to obtain a foam stabilizer.
[0086] Comparative Example 2
[0087] (1) SiO 2 Nanoparticles (15 g, D = 30 nm) were added to 50 mL of NaOH aqueous solution (pH = 9.0), and after being evenly dispersed, 1.6 g of N-2-aminoethyl-3-aminopropyltrimethoxysilane aqueous solution (100 mL) was added dropwise under the protection of inert gas. During the addition, 2 M NaOH aqueous solution was added to the system to maintain the pH value of the system at 9.0. After the addition was completed, the system was heated to 80 ° C, and then the reaction was carried out at a constant temperature for 20 hours. After the reaction was completed, the system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 1;
[0088] (2) Add H 2 O (100 mL), intermediate 1 (10.0 g) and 3-methacryloylpropyl-dimethyl-3-sulfonic acid propyl ammonium salt (8.8 g), stirred evenly, and nitrogen was bubbled for 30 min, then 0.87 g of potassium dipyrodecanoate (III) was added, and the temperature was raised to 50 ° C. After reacting for 6 h under continuous nitrogen flow, the nitrogen flow was stopped and the polymerization reaction was terminated. The system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 2;
[0089] (3) Add intermediate 2 (5.0 g) and water (40 mL) to a flask in sequence, adjust the pH value of the system to 9.0 with an aqueous NaOH solution, and add 10 mL of a hydrochloric acid solution (pH = 2.0) of isobutyltrimethoxysilane (0.5 g) dropwise under nitrogen protection. After the addition is completed, the system is heated to 70°C and reacted at this temperature for 20 hours. After separation, a solid is obtained, which is washed with water and dried to obtain a foam stabilizer.
[0090] Comparative Example 3
[0091] (1) SiO 2 Nanoparticles (15 g, D = 30 nm) were added to 50 mL of NaOH aqueous solution (pH = 9.0), and after being evenly dispersed, 1.6 g of 2,3-dihydroxypropyl propyl ether triethoxysilane aqueous solution (100 mL) was added dropwise under the protection of inert gas. During the addition, 2 M NaOH aqueous solution was added to the system to maintain the pH value of the system at 9.0. After the addition was completed, the system was heated to 80 ° C, and then the reaction was carried out at a constant temperature for 20 hours. After the reaction was completed, the system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 1;
[0092] (2) Add H 2 O (100 mL), intermediate 1 (10.0 g) and sodium 2-acrylamido-2-methylpropanesulfonate (8.8 g) were mixed and uniformly stirred, and nitrogen was bubbled for 30 min. Then 0.87 g of potassium dipyrodecanoate (III) was added, and the temperature was raised to 50°C. After reacting for 6 h under continuous nitrogen flow, the nitrogen flow was stopped and the polymerization reaction was terminated. The system was separated to obtain a solid, which was washed with water and dried to obtain intermediate 2;
[0093] (3) Add intermediate 2 (5.0 g) and water (40 mL) to a flask in sequence, adjust the pH value of the system to 9.0 with an aqueous NaOH solution, and add 10 mL of a hydrochloric acid solution (pH = 2.0) of isobutyltrimethoxysilane (0.5 g) dropwise under nitrogen protection. After the addition is completed, the system is heated to 70°C and reacted at this temperature for 20 hours. After separation, the solid is obtained, which is washed with water and dried to obtain a nano foam stabilizer.
[0094] Application Example 1
[0095] The foam stabilizer prepared in the above examples and comparative examples was mixed with a foaming agent to form a foaming agent flooding system, wherein the foaming agent was sodium α-olefin sulfonate (14C) with a content of 0.4wt%, the content of the foam stabilizer was 0.2wt%, and the balance was simulated brine (mineralization degree was 100000mg / L). The half-life and foam volume of natural gas foam were tested on a visual high-temperature and high-pressure foam evaluation instrument (temperature was 80°C and pressure was 12MPa), and the test results are shown in Table 1 below, wherein the control test was performed without adding the foam stabilizer.
[0096] Table 1
[0097] Serial number Foam stabilizer source Foaming agent Half-life (min) Foam volume (mL) 1 Example 1 Sodium α-olefin sulfonate 410 305 2 Example 2 Sodium α-olefin sulfonate 385 300 3 Example 3 Sodium α-olefin sulfonate 395 303 4 Example 4 Sodium α-olefin sulfonate 185 130 5 Example 5 Sodium α-olefin sulfonate 335 263 6 Example 6 Sodium α-olefin sulfonate 170 121 7 Example 7 Sodium α-olefin sulfonate 330 258 8 Example 8 Sodium α-olefin sulfonate 381 290 9 Example 9 Sodium α-olefin sulfonate 375 274 10 Example 10 Sodium α-olefin sulfonate 360 185 11 Comparative Example 1 Sodium α-olefin sulfonate 175 145 12 Comparative Example 2 Sodium α-olefin sulfonate 143 135 13 Comparative Example 3 Sodium α-olefin sulfonate 145 142 14 No foam stabilizer Sodium α-olefin sulfonate 140 142
[0098] The resistance factors of the system formed by the foam stabilizer and the foaming agent prepared in Example 1 and the control group (without the foam stabilizer) to natural gas are as follows: Figure 4The test conditions are as follows: temperature of 80°C, pressure of 12MPa, gas-liquid slug ratio of 1:1, core permeability of 125mDa, injection rate of 1mL / min, foaming agent content of 0.4%, foam stabilizer content of 0.2%, and simulated salt water dispersion system (mineralization of 100000mg / L).
[0099] Application Example 2
[0100] The difference from the application example is that the foaming agent is sodium dodecyl sulfate with the same content. The test results are shown in Table 2 below.
[0101] Table 2
[0102] Foam stabilizer source Foaming agent Half-life (min) Foam volume (mL) Example 1 Sodium Lauryl Sulfate 251 481 Example 2 Sodium Lauryl Sulfate 235 402 No foam stabilizer Sodium Lauryl Sulfate 90 166
[0103] Application Example 3
[0104] The difference from the application example is that the foaming agent is the same content of alkyl polyglycoside (APG0814). The test results are shown in Table 3 below.
[0105] Table 3
[0106] Foam stabilizer source Foaming agent Half-life (min) Foam volume (mL) Example 1 Alkyl glycoside 362 320 Example 2 Alkyl glycoside 314 275 No foam stabilizer Alkyl glycoside 113 107
[0107] From the above description, it can be seen that the above embodiment of the present invention achieves the following technical effects: the above preparation method is prepared by first grafting a silane coupling agent initiator on inorganic nanoparticles, then under the action of a catalyst, a hydrophilic monomer undergoes polymerization reaction on the particle surface, and finally the particles are grafted with a hydrophobic silane coupling agent. The nano foam stabilizer prepared by the above preparation method not only has a hydrophobic group that can produce a hydrophobic interaction with the tail of the foaming agent, but also has an electrically neutral hydrophilic polymer group on the particles, which can play a role in temperature and salt resistance on the one hand; on the other hand, compared with some anionic polymers, such as 2-acrylamide-2-methylpropanesulfonic acid sodium polymer, it is beneficial to reduce or avoid charge repulsion with the surfactant head group, promote the adsorption of nanoparticles at the gas-liquid interface, and thus help improve the stability of the foam. In this way, when it is carried by injected water, it is conducive to its smooth migration in high-temperature and high-mineralization reservoirs, and foam is generated deep in the formation during the gas injection process. When it is used in combination with a foaming agent, it can have a higher resistance factor than using a foaming agent alone, achieving the functions of deep plugging and delaying gas channeling. Moreover, the reactions in the preparation method are all water-phase reactions, no organic solvents are used, and the pollution to the environment is small.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A foam stabilizer raw material system, characterized in that: include: Inorganic nanoparticles, organic monomers, initiators, catalysts, and hydrophobic modifiers; The organic monomer has an electrically neutral hydrophilic group.
2. The raw material system according to claim 1, characterized in that: The inorganic nanoparticles are any one or more of nano-SiO2, nano-TiO2, nano-ZnO and nano-Al2O3. Preferably, the particle size of the inorganic nanoparticles is 20 to 100 nm. Preferably, the organic monomer includes any one or more of 2,3-dihydroxypropyl methacrylate, N-(2,3-dihydroxypropyl) methacrylamide, 3-methacryloylpropyl-dimethyl-3-sulfonic acid propyl ammonium salt and 3-methacrylate propyl-dimethyl-3-sulfonic acid propyl ammonium salt; Preferably, the initiator is 2,3-dihydroxypropyl propyl ether triethoxysilane; Preferably, the hydrophobic modifier includes any one or more of trimethylmonoethoxysilane, dimethyldiethoxysilane, isopropyltriethoxysilane, isobutyltrimethoxysilane and n-octyltriethoxysilane; Preferably, the catalyst comprises any one or more selected from potassium diperiodate copper and potassium diperiodate nickel; Preferably, the raw material system comprises 5 to 15 parts by weight of inorganic nanoparticles, 1.0 to 2.0 parts by weight of an initiator, 3.0 to 10.0 parts by weight of an organic monomer, 0.3 to 0.6 parts by weight of a catalyst, and 0.8 to 2.0 parts by weight of a hydrophobic modifier; Preferably, the raw material system further includes a reaction medium, and the reaction medium is water.
3. A method for preparing a nano foam stabilizer by using the raw material system according to claim 1 or 2, characterized in that: include: Step S1, dispersing the inorganic nanoparticles in water, adjusting the pH value to be alkaline, adding the initiator to the system to form a first mixed solution for reaction, and after the reaction is completed, separating the solid to obtain a first intermediate; Step S2, dispersing the first intermediate and the organic monomer in water, introducing an inert gas to remove oxygen, adding a catalyst to form a second mixed solution for polymerization reaction, and separating the solid after the polymerization reaction to obtain a second intermediate; Step S3, dispersing the second intermediate in water, adding a hydrophobic modifier to form a third mixed solution for a modification reaction, and obtaining a nano foam stabilizer after the modification reaction is completed.
4. The method according to claim 3, characterized in that In the step S1, the mass percentage of the inorganic nanoparticles in the mixed solution is 5-15%, and the mass percentage of the initiator is 1.0-2.0%; Preferably, the pH value is 8.0 to 9.0; Preferably, the initiator is added in the form of an initiator aqueous solution, preferably the initiator aqueous solution is added in the form of dropwise addition, preferably an alkaline solution is added during the dropwise addition to adjust the pH value to alkaline, and more preferably, the pH value is adjusted to 8.0-9.0 during the dropwise addition; Preferably, the alkaline solution is any one or more of a sodium hydroxide aqueous solution or a sodium carbonate aqueous solution.
5. The method according to claim 4, characterized in that The reaction temperature in step S1 is 70-80° C., preferably, after the initiator aqueous solution is added dropwise, the temperature is raised to the reaction temperature; Preferably, the reaction time is 15 to 20 hours.
6. The method according to claim 3, characterized in that: The mass fraction of the first intermediate in the second mixed liquid is 5-15%, the mass fraction of the organic monomer is 3.0-10.0%, and the mass fraction of the catalyst is 0.3-0.6%; Preferably, the polymerization reaction temperature is 50-60° C., and preferably, the polymerization reaction time is 5-8 h.
7. The method according to claim 3, characterized in that The mass fraction of the second intermediate in the third mixed solution is 8-15%, and the mass fraction of the hydrophobic modifier is 0.5-2.0%; Preferably, the temperature of the modification reaction is 60-70° C., and preferably, the time of the modification reaction is 20-25 h.
8. A nano foam stabilizer, characterized in that: Prepared by the method described in any one of claims 3 to 7.
9. A foam flooding system, characterized in that: Including the nano foam stabilizer as described in claim 8.
10. Use of the foam flooding system according to claim 9 in gas flooding, wherein the gas is preferably natural gas.
Citation Information
Patent Citations
Method for preparing functional particles with high grafting degree
CN101857667A
Nanoparticle-added composite foam system used for oil and gas field and preparation method thereof
CN102746841A
Water-soluble low-modulus acrylic resin adhesive and preparation method thereof
CN112409962A
Water-insoluble grafted polysiloxane copolymer und use thereof as a defoamer and a de-aerating agent in non-aqueous oils
EP1634940A1
Cited By
Compound foam stabilizer, foam concrete and preparation method of foam concrete
CN120590091A
A foam stabilizer based on graded modification of enteromorpha and a preparation method and application thereof
CN121343578B